2021
DOI: 10.3389/fnut.2021.738045
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nutritional Status Score as a Predictive Marker of In-hospital Mortality in Older Adult Patients

Abstract: The controlling nutritional status (CONUT) score assesses nutritional status and is associated with short- and long-term prognoses in some diseases, but the significance of the CONUT score for the prediction of in-hospital mortality in older adults is unknown. The purpose was to determine the importance of the CONUT score for the prediction of in-hospital mortality, short-term complications, length of hospital stay, and hospital costs in older adults. Our retrospective cohort study analyzed data from 11,795 ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 44 publications
3
20
1
1
Order By: Relevance
“…There are a few general population-based studies that compare LDL-C levels and mortality risk between sexes. Both NHANES 1994-2014 data from the US ( Liu et al., 2021a ; Liu et al., 2021b ) and the Ibaraki Prefecture Health Study of Japan ( Noda et al, 2010 ) found that the lowest levels of LDL-C (<70 and <80 mg/dL, respectively) increased all-cause mortality risk in both men and women similar to the results of our study. In the Japanese study above ( Noda et al, 2010 ), higher, but not lower concentrations of LDL-C were associated with increased mortality risk from coronary heart disease for men, but not for women.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There are a few general population-based studies that compare LDL-C levels and mortality risk between sexes. Both NHANES 1994-2014 data from the US ( Liu et al., 2021a ; Liu et al., 2021b ) and the Ibaraki Prefecture Health Study of Japan ( Noda et al, 2010 ) found that the lowest levels of LDL-C (<70 and <80 mg/dL, respectively) increased all-cause mortality risk in both men and women similar to the results of our study. In the Japanese study above ( Noda et al, 2010 ), higher, but not lower concentrations of LDL-C were associated with increased mortality risk from coronary heart disease for men, but not for women.…”
Section: Discussionsupporting
confidence: 86%
“…Each year’s lowest albumin and Hb were collected to calculate the mean of the annual mean of each to prevent overestimation of those values after replacement. Mean albumin levels were grouped into ≥3.5, 3.0−3.4, 2.5−2.9, and <2.5 g/dL ( Liu et al., 2021a ; Liu et al., 2021b ). Hypoglycemia was identified in patients with fasting or postprandial plasma or POC glucose values <70 mg/dL on any occasion during the study period ( Draznin et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The controlling Nutritional Status (CONUT) score has been reported to be a simple and efficient screening tool for evaluating malnutrition status, especially for early detection and ongoing monitoring of nutritional status in hospitalized patients ( 16 ). Current studies suggest that CONUT is associated with short- and long-term prognoses in some diseases ( 9 , 14 , 15 , 17 ). The CONUT score is calculated based on the parameters of serum albumin, total cholesterol and, total lymphocyte levels, consisting of an immune-nutritional index reflecting protein/lipid metabolism and immunocompetence ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…A positive relationship between CONUT score and SGA was also reported previously [ 29 ]. In addition, previous studies showed that the CONUT score is a useful marker for mortality [ 30 , 31 ], healing of foot ulcers [ 32 , 33 ], and subclinical atherosclerosis [ 34 ]. In the present study, multivariate logistic regression analysis indicated that the CONUT score was significantly associated with a high-risk foot in the older group, with or without statin use.…”
Section: Discussionmentioning
confidence: 99%